Alteration of volcanic deposits in the ANDRILL AND-1B core: Influence of paleodeposition, eruptive style, and magmatic composition - Alessio Di Roberto; Francesco Iacoviello; Massimo Pompilio; Giovanna Giorgetti (Geosphere, 2013)
Alteration minerals, assemblages, and textures were studied in a 175-m-thick volcanic sequence found between 759.32 and 584.19 m below seafloor within the 1285-m-long ANDRILL (Antarctic Geological Drilling project) McMurdo Ice Shelf core (MIS AND-1B). Three main alteration zones were identified through the application of different analytical methods (optical and scanning electron microscopy, electron microprobe, and X-ray diffraction). Alteration zoning is guided by the texture of the volcanic deposits, which is in turn determined by the eruptive style, transport mechanisms, and paleodepositional conditions. In particular, alteration reflects the evolution of paleodepositional conditions from submarine or shallow water to subaerial due to the growth of a nearby volcanic edifice. The general alteration trend is also influenced by the contribution of volcanogenic sediments derived from the reworking of silica-rich pyroclasts from earlier volcanic activity.